Markers of oxidative damage of nucleic acids and proteins among workers exposed to TiO2 (nano) particles - Pelclova, D; Zdimal, V; Fenclova, Z; Vlckova, S; Turci, F; Corazzari, I; Kacer, P; Schwarz, J; Zikova, N; Makes, O; Syslova, K; Komarc, M; et al. (Occupational and environmental medicine, 2016)
OBJECTIVE: The use of nanotechnology is growing enormously and occupational physicians have an increasing interest in evaluating potential hazards and finding biomarkers of effect in workers exposed to nanoparticles. METHODS: A study was carried out with 36 workers exposed to (nano)TiO2 pigment and 45 controls. Condensate (EBC) titanium and markers of oxidation of nucleic acids (including 8-hydroxy-2-deoxyguanosine (8-OHdG), 8-hydroxyguanosine (8-OHG), 5-hydroxymethyl uracil (5-OHMeU)) and proteins (such as o-tyrosine (o-Tyr), 3-chlorotyrosine (3-ClTyr) and 3-nitrotyrosine (3-NOTyr)) were analysed from samples of their exhaled breath. RESULTS: In the production workshops, the median total mass 2012 and 2013 TiO2 concentrations were 0.65 and 0.40 mg/m(3), respectively. The median numbers of concentrations measured by the scanning mobility particle sizer (SMPS) and aerodynamic particle sizer (APS) were 1.98 × 10(4) and 2.32 × 10(4) particles/cm(3), respectively; and about 80% of those particles were smaller than 100 nm in diameter. In the research workspace, lower aerosol concentrations (0.16 mg/m(3) and 1.32 × 10(4) particles/cm(3)) were found. Titanium in the EBC was significantly higher in production workers (p<0.001) than in research workers and unexposed controls. Accordingly, most EBC oxidative stress markers, including in the preshift samples, were higher in production workers than in the two other groups. Multiple regression analysis confirmed an association between the production of TiO2 and the levels of studied biomarkers. CONCLUSIONS: The concentration of titanium in EBC may serve as a direct exposure marker in workers producing TiO2 pigment; the markers of oxidative stress reflect the local biological effect of (nano)TiO2 in the respiratory tract of the exposed workers.
Keywords: dospělí; DNA Damage; velikost částic; Work; biologické markery; oxidační stres; Biomarkers; Adult; mladý dospělý; Particle Size; Nanoparticles; Oxidative Stress; lidé; Occupational Exposure; Titanium; nukleové kyseliny; Particulate Matter; Breath Tests; nanočástice; Proteins; titan; Nucleic Acids; Humans; oxidace-redukce; proteiny; poškození DNA; Male; pracovní expozice; Oxidation-Reduction; práce; Young Adult; lidé středního věku; dechové testy; mužské pohlaví; Middle Aged; pevné částice